The Contribution of Physical Education in the Correction of Primary School Students’ Dysgraphia - Victoria RAZMIREȚ; Gheorghe BRANIȘTE (ACROSS)
The actuality of the discussed subject is determined by the valorization of physical education activities in the didactic process to correct primary school students' dysgraphia. At present, physical development is little exploited in this sense. Physical education classes are limited and as a result the number of students with learning disorders, especially with dysgraphia, increases significantly. From this point of view, we note the need to capitalize on physical education, as a component of the instructional-educational process in the school which aims to contribute to the improvement of the physical and intellectual development; of the students' motor capacity. The physical education process in primary school does not have a program for correcting dysgraphia and the number of hours for the physical education classes is limited, a fact that aggravates both writing disorders and the development of the student's personality.